THREE-DIMENSIONAL COMPUTATIONAL FLUID DYNAMICS ANALYSIS OF BUOYANCY-DRIVEN NATURAL VENTILATION AND ENTROPY GENERATION IN A PRISMATIC GREENHOUSE - Aich, Walid; Kolsi, Lioua; Borjini, Mohamed N.; Al-Rashed, Abdullah A. A. A.; Ben Aissia, Habib; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Vinca Inst Nuclear Sci, 2018)
A computational analysis of the natural ventilation process and entropy generation in 3-D prismatic greenhouse was performed using CFD. The aim of the study is to investigate how buoyancy forces influence air-flow and temperature patterns inside the greenhouse having lower level opening in its right heated fa ade and also upper level opening near the roof top in the opposite cooled facade. The bottom and all other walls are assumed to be perfect thermal insulators. Rayleigh number is the main parameter which changes from 10(3) to 10(6) and Prandtl number is fixed at Pr = 0.71. Results are reported in terms of particles trajectories, iso-surfaces of temperature, mean Nusselt number, and entropy generation. It has been found that the flow structure is sensitive to the value of Rayleigh number and that heat transfer increases with increasing this parameter. Also, it have been noticed that, using asymmetric opening positions improve the natural ventilation and facilitate the occurrence of buoyancy induced upward cross air-flow (low-level supply and upper-level extraction) inside the greenhouse.
Keywords: 3-D CFD; natural ventilation; prismatic greenhouse; heat transfer; entropy generation